2015
DOI: 10.1186/s13075-015-0810-3
|View full text |Cite
|
Sign up to set email alerts
|

Impaired function of endothelial progenitor cells in children with primary systemic vasculitis

Abstract: IntroductionPreviously, we demonstrated that children with active systemic vasculitis (SV) have higher circulating CD34 + CD133 + KDR+ endothelial progenitor cells (EPC); the function of these EPCs, and their relationship with disease activity in vasculitis remains largely unexplored. We hypothesized that although EPC numbers are higher, EPC function is impaired in active SV of the young. The aims of this study were therefore to: 1. investigate the relationship between disease activity and EPC function in chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 56 publications
2
11
0
Order By: Relevance
“…Our preliminary observations are in keeping with similar studies in systemic vasculitis that suggest that attempts at endothelial repair may be thwarted (for reasons as yet unidentified) in children with the most severe vasculitis [ 11 ]. The same may also be true of children with recurrent AIS.…”
Section: Discussionsupporting
confidence: 88%
“…Our preliminary observations are in keeping with similar studies in systemic vasculitis that suggest that attempts at endothelial repair may be thwarted (for reasons as yet unidentified) in children with the most severe vasculitis [ 11 ]. The same may also be true of children with recurrent AIS.…”
Section: Discussionsupporting
confidence: 88%
“…EPCs migrate from bone marrow to the lesions. Chronic inflammation during vasculitis may impair EPC function and reduce endothelial repair capacity (215). …”
Section: Endothelial Response To Gcs In Vasculitismentioning
confidence: 99%
“…It has been reported that stem cells derived from animals or patients with physiological stresses, such as systemic inflammation, have impaired regenerative activity (30)(31)(32)(33). Because many patients with cardiac diseases, especially heart failure, suffer from these physiological stresses, we have hypothesized that cardiac cell-secreted exosomes derived from these patients may have impaired therapeutic activity, or possibly make the condition worse.…”
Section: Introductionmentioning
confidence: 99%